A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN USING PAST EXPRESSION (COMPLEX SENTENCES) - Fitra, Harry; Azhar, Fadly; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research investigates the ability of the fourth semester students of English department study program FKIP universitas Riau Pekanbaru in using past expression (complex sentences). The population of this research was the fourth semester students of English department study program FKIP universitas Riau Pekanbaru in academic year of 2018/2019. There were 30 students who participate as the sample of this research. The students are tested using a simple test. The result of the test given was then classified into certain categories. The test results of 30 students shows that 6 students (20%) are in good to excellent category, 8 students (26,67%) are in good to excellent level, 8 students (26,67%) at average to good level, 8 students (26,67%) in poor to average level, and last 8 student (26,67%) in poor level. In addition, the average score of the students in past expression (complex sentences) is 61,16. It means that the students’ ability in past expression(complex sentences) was in the average to good level. Based on the tests, it can be concluded that the fourth semester students of English department study program FKIP universitas Riau Pekanbaru already were in average to good ability in past expression(complex sentence). Researcher recommended the students and other researchers to conduct similar research to get further information.Key Words: Ability, Past Expression, and Complex Sentences